Avaliação do ciclo de vida no beneficiamento de malha : estudo de caso em uma tinturaria no estado do Paraná - Maia, Elaine Regina Brito (2013)
A life cycle assessment is a tool that consists of selecting and evaluating the inputs and outputs of the processes, enabling the identification of the environmental impacts of a product system throughout its life cycle. This paper presents the evaluation of the life cycle applied to a textile benefaction industry, responsible for the process of dyeing and finishing of knitted fabrics, located in the northwest of Paraná. The goal of this paper is to characterize the potential environmental impacts in the benefaction process related to the use of natural resources, as well as the pollutants emitted by this process. For effective research, data were collected regarding the production of a month of the year 2013. For the application of life cycle assessment was used SimaPro ® software, version 7.3.3. The method used to analyze the register was RECIPE midpoint and the categories which were analyzed were terrestrial acidification, climate change, marine ecotoxicity, the depletion of fossil and human toxicity. Two forms of impact assessment were carried out: one, which considered the transport of the products used in the process of benefaction and another which did not consider this factor . The results regarding the first form of evaluation showed that the road transport, in which the delivery trajectory of salt is considered and the road transport, responsible for the trajectory of other inputs used in dyeing, were the items that provided greater impact on the process of benefaction of the knitted fabrics. This impact is due to the amount of atmospheric emissions from the burning of fossil fuel. Assessing the impacts without considering transport, the results showed the use of wood chips as responsible for the impacts in the viii categories acidification, human toxicity and ecotoxicity marine. Concerning the depletion of fossil category, the factor that caused impact was the use of chemicals. As for the climate change category , the highest factor of impact was the electricity.